Improved clinical outcomes after arthroscopic partial rotator cuff repair with rotator interval shift for the treatment of massive irreparable anterior L-shaped rotator cuff tears - Yu-Sheng Chen; Fa-Chuan Kuan; Wei-Ren Su; Chih-Kai Hong; Yueh Chen; Kai-Lan Hsu (Journal of Orthopaedic Surgery and Research)
Abstract Purpose The treatment of massive anterior L-shaped rotator cuff tears (RCTs) remains challenging. This study focused on restoration of humeral head coverage by superiorly repositioning the rotator interval tissue. The study aimed (1) to present the short-term clinical and radiological outcomes of arthroscopic partial repair combined with rotator interval shift and (2) to identify risk factors associated with failure in restoring superior humeral head coverage. Method A retrospective review was conducted on arthroscopic rotator cuff repairs performed by a single surgeon between January 2018 and December 2022. Patients with irreparable anterior L-shaped tears who underwent partial repair and rotator interval shift and had a follow-up of 2 years were included. The measured outcomes included range of motion, pain, and functional scores. Humeral head coverage was evaluated using magnetic resonance imaging (MRI) at 6 months postoperation, and patients were classified as either healed or having a retear. Logistic regression analysis was conducted to identify factors associated with retears. Results The study included 45 patients (19 men and 26 women) with an average age of 66.53 ± 6.70 years. After 2 years, significant improvements were observed in forward elevation (from 77.73 ± 40.96 to 156.11 ± 25.89), abduction (from 82.89 ± 43.78 to 161.33 ± 22.90), American Shoulder and Elbow Surgeons scores (from 43.24 ± 15.77 to 83.16 ± 10.27), and Constant–Murley scores (from 44.98 ± 15.76 to 86.38 ± 10.02; all p < 0.001). Visual analog scale pain scores also decreased (from 7.09 ± 2.35 to 1.29 ± 1.70). MRI results at 6 months showed that 30 of 45 patients (66.7%) had healed, while the retear rate was 33.3%. The acromiohumeral interval (AHI) was identified as the only factor significantly associated with retear. The odds ratio for predicting retear in patients with a preoperative AHI of < 5.0 mm was 5.50. (95% CI: 1.43–21.10, p = 0.013). Conclusion Arthroscopic partial repair combined with rotator interval shift is an effective treatment option for irreparable anterior L-shaped RCTs, demonstrating favorable short-term clinical and radiological outcomes. However, patients with a preoperative AHI of less than 5 mm are at greater risk of retear, potentially leading to reduced postoperative range of motion. Level of evidence Level IV, case series.